Synthesis of resilient hybrid hydrogels using UiO-66 MOFs and alginate (hydroMOFs) and their effect on mechanical and matter transport properties. (1st January 2021) - de Lima, Hugo H.C.; da Silva, Cleiser T.P.; Kupfer, Vicente. L.; de C. Rinaldi, Jaqueline; Kioshima, Erika S.; Mandelli, Dalmo; Guilherme, Marcos R.; Rinaldi, Andrelson W.
Highlights: Organic–inorganic hybrid hydrogel using alginate and UIO-66 AA was synthetized. UIO 66 MOFs with different crystal sizes (600, 1500, and 2500 nm) were prepared. The properties of the materials depend on the size and amount of UIO-66 crystals. The hybrid materials showed reduced burst release and mechanical robustness. Cytotoxicity screening indicated a promising biocompatible architecture. Abstract: Herein, we report the preparation of an organic–inorganic hybrid hydrogel architecture using vinyl alginate and UiO-66 MOFs (metal-organic frameworks) modified with acrylic acid (AA) UiO-66AA. UiO-66 MOFs with different crystal sizes (600, 1500, and 2500 nm) were synthesized and the effect on the mechanical and transport properties of the resulting materials, such as water absorption capacity and drug release, were evaluated. HydroMOF showed higher water absorption capacity than the pure hydrogel and enhanced mechanical properties, which depend on crystal size and the amount of UiO-66AA MOF used. The initial release rate of drug (burst release) from hydroMOFs was lower when small-sized crystals or a small amount of large-sized crystals were used; thus these are essential in changing half-life values of release rates. Finally, the cytotoxicity screening successfully showed that hydroMOFs are promising biocompatible compounds proven to have the advantages of minimized burst release and mechanical robustness.